A Review on Differential Isotope-coded Derivatization Reagents for LC-API-MS Analyses - Sun, Zhiwei; Sun, Haiyi; Li, Hongtao; You, Jinmao; Xia, Lian (Current Analytical Chemistry, 2014)
High-performance liquid chromatography coupling with atmospheric pressure ionization mass spectrometry (LC–API–MS) has been widely used in the pharmaceutical industry, clinical research, environmental science, metabolomics studies and so on. However, LC-API-MS often suffers from the matrix effect in its applications in complex samples. Matrix effects can heavily affect reproducibility, linearity, and accuracy of the method leading to erroneous quantitation. The use of isotope-labeled analyte as internal standards provides an efficient solution to overcome matrix effects in LCAPI- MS analysis. However, the isotope-labeled standards are expensive and not always available, especially in the analysis of large numbers of analytes. In recent years, the stable isotope-coded derivatization reagents, as an alternative way, have been used to quantify small molecules in LC-API-MS analysis of complex samples. In this review, an overview of differential isotope-coded derivatization reagents is presented, focusing on the applications to low molecular weight compounds by LC-API-MS. The recently reported isotope-coded derivatization reagents were summarized in category of their target analytes, specifically peptides, amines, phenols, carboxylic acids, aldehyde or ketone, saccharides and thiols. It indicates that isotope-labeled derivatization reagent would have an increasingly wide range of applications in the LC-APIMS analysis.
Keywords: isotope-coded derivatization reagent